2011
DOI: 10.1074/jbc.m111.232876
|View full text |Cite
|
Sign up to set email alerts
|

Direct Evidence for Methyl Group Coordination by Carbon-Oxygen Hydrogen Bonds in the Lysine Methyltransferase SET7/9

Abstract: SET domain lysine methyltransferases (KMTs) are S-adenosylmethionine (AdoMet)-dependent enzymes that catalyze the site-specific methylation of lysyl residues in histone and nonhistone proteins. Based on crystallographic and cofactor binding studies, carbon-oxygen (CH⅐⅐⅐O) hydrogen bonds have been proposed to coordinate the methyl groups of AdoMet and methyllysine within the SET domain active site. However, the presence of these hydrogen bonds has only been inferred due to the uncertainty of hydrogen atom posit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
90
0
1

Year Published

2012
2012
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 58 publications
(96 citation statements)
references
References 68 publications
5
90
0
1
Order By: Relevance
“…One possible explanation for BIEs >1 is a change in local electrostatics that fails to be accompanied by any overall decrease in the distance between the methyl donor (S + ) and acceptor (represented by the hydroxyl group of 8-hydroxyquinoline). We note that in a related methyl transfer system, SET7/9, X-ray crystallography and NMR of the binary complex have led to the proposal of ground state hydrogen bonding between the C-H of the methyl group in AdoMet and electronaccepting protein side chain(s) (45,46). A role for such putative C-H···O bonding in reducing vibrational frequencies at the transferred methyl group would be consistent with BIEs larger than unity, with the caveat that the elevated BIE data presented herein are for a different enzyme family and only occur in the presence of the relatively weak binding inhibitor 8-hydroxyquinoline.…”
Section: Discussionmentioning
confidence: 99%
“…One possible explanation for BIEs >1 is a change in local electrostatics that fails to be accompanied by any overall decrease in the distance between the methyl donor (S + ) and acceptor (represented by the hydroxyl group of 8-hydroxyquinoline). We note that in a related methyl transfer system, SET7/9, X-ray crystallography and NMR of the binary complex have led to the proposal of ground state hydrogen bonding between the C-H of the methyl group in AdoMet and electronaccepting protein side chain(s) (45,46). A role for such putative C-H···O bonding in reducing vibrational frequencies at the transferred methyl group would be consistent with BIEs larger than unity, with the caveat that the elevated BIE data presented herein are for a different enzyme family and only occur in the presence of the relatively weak binding inhibitor 8-hydroxyquinoline.…”
Section: Discussionmentioning
confidence: 99%
“…However, limited efforts have been made to explore experimentally the (S N 2) TS of PKMT-catalyzed methylation. Recent evidence from static PKMT structures and dynamic NMR chemical shifts suggests the existence of equatorial noncanonical CH-O interaction between the sulfonium methyl moiety of SAM and the oxygens of active-site amino acid residues of PKMTs (36)(37)(38), although it remains to examine how the equatorial CH-O interaction participates in the formation of the TS of PKMT-catalyzed methylation reaction.…”
Section: Significancementioning
confidence: 99%
“…The recent elucidation of noncanonical CH-O interaction could shed light on an alternative, but mutually nonexclusive mechanism for the constrained TS of protein methyltransferases (36)(37)(38). In the context of the TS of SET8-catalyzed H4K20 monomethylation, the sulfonium-methyl group of SAM is expected to form three equatorial noncanonical CH-O interactions with the two backbone amide oxygens of Cys270 and Arg295 and the phenolic oxygen of the side chain of Tyr336 (Fig.…”
Section: Computational Modeling Of Transition State Of Set8-catalyzedmentioning
confidence: 99%
“…The methyl donor SAM binds in a pocket at the junction of core SET, SET-I and post-SET, which make extensive contacts to SAM including hydrogen bonds and van der Waals contacts. Other important interactions involve tyrosine and carbonyl oxygens that form CH···O hydrogen bonds with the SAM methyl group [126].…”
Section: Structural Studies Of Nsd Ash1l and Setd2 Set Domains Demonstmentioning
confidence: 99%
“…The methyl donor SAM binds in a pocket at the junction of core SET, SET-I and post-SET, which make extensive contacts to SAM including hydrogen bonds and van der Waals contacts. Other important interactions involve tyrosine and carbonyl oxygens that form CH···O hydrogen bonds with the SAM methyl group [126].The autoinhibitory loop must undergo a significant conformational change to accommodate nucleosome substrate, and interestingly this loop undergoes dynamics even without nucleosome present. Molecular dynamics simulations, crystallographic and NMR studies have shown that the NSD1 and ASH1L autoinhibitory loops experience conformational heterogeneity in the absence of nucleosome substrate [127,128].…”
mentioning
confidence: 99%